The relationship between intrinsic motivation and internship work performance of hospitality interns at selected 5 star Langkawi hotels / Nurul Shafini Ibrahim and Husna Samanuri - Ibrahim, Nurul Shafini; Samanuri, Husna (Faculty of Hotel and Tourism, 2018)
This study aims to examine the relationship between intrinsic motivational factors and work performance of hospitality interns. Descriptive research design using quantitative method through self-administrated questionnaire was employed for the purpose of this investigation. 81 questionnaires to respondents (i.e., 30 from The Ritz Carlton Langkawi, 21 from The Andaman Langkawi, 19 from The Westin Langkawi Resort & Spa and 11 from St Regis Langkawi) were successfully distributed. All data were keyed in into SPSS Version 22.0 and analyzed using suitable statistical analyses to respond this study’s research objectives; i) to identify which intrinsic motivational factor that most correlate to the hospitality intern’s performance (ROl), and ii) to understand how the most influence of intrinsic motivational factors does explain the hospitality's intern performance (R02). Result revealed that there is significant relationship between intrinsic motivational factors to the hospitality intern’s performance. Further analysis has showed that intrinsic motivational have influence hospitality's intern performance. Therefore, this study based on five selected five-star hotels in Langkawi suggested that another imperative study focused on leadership of the academician in providing training and guide student to be competent in future undertaking.